ASSESSMENT OF HLA-B27 EXPRESSION BY FLOW CYTOMETRY AND ITS CLINICAL RELEVANCE IN ANKYLOSING SPONDYLITIS - Quang Đẳng, Nguyễn; Thị Thanh Thuý, Huỳnh; Thị Mỹ Linh, Nguyễn (Journal of Health and Aging, 2026)
Ankylosing spondylitis (AS) is a chronic inflammatory disease strongly associated with the genetic marker HLA-B27. HLA-B27 testing plays an important role in supporting early diagnosis. Flow cytometry is a novel method with high potential for detection of HLA-B27. To determine the prevalence of HLA-B27 positivity and negativity among AS patients and to evaluate its association with biological characteristics within the study population. A retrospective descriptive study was conducted at Thong Nhat Hospital from January to July 2025 on patients diagnosed with AS based on ICD code M45. HLA-B27 testing was performed using the flow cytometry technique. Data were analyzed using descriptive statistics and correlation analysis via Microsoft Excel 2021. Among 248 patients diagnosed with AS (ICD M45), females were predominant (male:female ratio = 1:1.5). The average age of the cohort was 44.6 ± 14.9 years. The rate of HLA-B27 positivity was 12% (30/248), significantly lower than in previous studies. Patients with HLA-B27 positivity had a younger mean age at disease onset compared to the negative group (40.9 ± 15.4 vs. 45.1 ± 14.8 years; p = 0.048). No statistically significant difference in gender distribution was observed between the two groups (p > 0.05), although a higher proportion of females was noted in the HLA-B27 negative group. In Conclusions, The low HLA-B27 positivity rate in this study may reflect population characteristics and broader screening criteria. HLA-B27 positivity was associated with younger age at disease onset, suggesting its role not only in diagnosis but also in clinical presentation. Flow cytometry proved effective in detecting HLA-B27 and shows potential for broader clinical application.
Keywords: flow cytometry